"Together, we can do it all!": narratives of masculinity, sport and exercise amongst physically wounded Danish veterans. Issue 5 (19th October 2020) - Evans, Adam B.; Andreassen, Sofie M. N.; Virklund, Amanda W.
ABSTRACT: Transitions from military into civilian life can be problematic, particularly when caused by service-related injury. Studies suggest the management of psychological and physical injury requires care and management beyond initial rehabilitation. Narrative studies with predominantly British and American veterans have highlighted the role sport and exercise can play in this management. Knowledge of the experiences of veterans among their coalition allies in the Afghanistan and Iraq conflicts are few, however. This study presents results of a narrative analysis which focused upon 7 physically injured Danish veteran's experiences of the Dansk Idrætsforbund's 'Soldier Project'. Taking a feminist-inspired narrative approach, we conducted field observations and interviews combined with visual elicitation to generate data relating to participants' experiences of masculinity, injury, rehabilitation and the soldier project. We reconstituted our data into narrative vignettes, which represent common themes in narratives across multiple participants' stories. Participants' narratives shifted from idealised presentations of embodied, hegemonic military identities prior to the injury, through a period of narrative disruption, chaos and loss of identity following injury. Participants then highlighted the challenge presented by 'picking up the thread' of their embodied narratives and re-establishing body-relatedness through participation in the Solider Project. Here, complex and often contradictory conceptualisations of masculinity co-existed. Some were restitutional, expressed through participation in aggressive, full-contact sports which were considered 'new missions' or 'training'. Conversely, quest narratives and more communicative body actions were evident as participants sought to find new activities through which to express new masculine identities. The implications of our findings for similar programmes are discussed.